Federalismo cooperativo no Brasil: da Constituição de 1988 aos sistemas de políticas públicas - Franzese, Cibele (2010)
This research explores the reciprocal relationship between federalism and social policies in Brazil, analyzing the public policies systems in health, education and social care. The thesis is based on the international literature on federalism and Welfare State to build a theoretical framework that examines the systems of public policy as a matrix, which expands the federal cooperation, based on intergovernmental negotiation. The thesis argues that this model results from the interaction between the institutional design of the Brazilian Constitution of 1988 and the governmental efforts to universalize social policies, which have been lead by federal actions, since the second half of the 1990s. This study aims to offer a new approach to federalism in Brazil that is not based on the traditional dichotomy between centralization and decentralization that prevails in the national debate. Moreover, it wants to call attention to the systems of public policy as new institutional arrangements that allow the combination of nationalization social policy and fortification of federal negotiation.